Obesity-Induced Inflammation Is Associated with Alterations in Subcellular Zinc Pools and Premature Mammary Gland Involution in Lactating Mice. Issue 9 (22nd July 2015) - Hennigar, Stephen R; Velasquez, Vanessa; Kelleher, Shannon L
Abstract: Background: Lactation failure is common in overweight and obese women; however, the precise mechanism remains unknown. Objective: We tested the hypothesis that obesity-induced inflammation in the mammary gland (MG) redistributes subcellular zinc pools to promote cell death of mammary epithelial cells (MECs) and premature involution. Methods: Female DBA/2J mice were fed a high-fat (obese; 45% kcal from fat, n = 60) or control diet (lean; 10% kcal from fat, n = 50) for 5 wk and bred. MG cytokines and macrophage infiltration were determined by reverse transcriptase-polymerase chain reaction and F4/80 staining, respectively. Zinc concentration was analyzed by atomic absorption spectroscopy, and zinc transporters and markers of endoplasmic reticulum (ER) stress, autophagy, and involution were measured by immunoblot. To confirm effects of inflammation, tumor necrosis factor-α (TNF) or vehicle was injected into adjacent MGs of lean lactating C57BL/6 mice ( n = 5) and cultured MECs (HC11 cells) were treated with TNF in vitro. Results: Seventy-seven percent of obese mice failed to lactate (lean: 39%; P < 0.001). Obese mice capable of lactating had greater macrophage infiltration (obese: 135 ± 40.4 macrophages/mm 2 ; lean: 63.8 ± 8.9 macrophages/mm 2 ; P < 0.001) and elevated TNF expression ( P < 0.05), concurrent with lower zrt- irt-like protein 7 abundance ( P < 0.05) and higher ER zinc concentration (obese: 0.36 ± 0.004 μg Zn/mg protein; lean: 0.30 ± 0.02 μg Zn/mg protein; P < 0.05) compared with lean mice. Heat shock protein 5 (HSPA5) expression ( P < 0.05) was suppressed in the MG of obese mice, which was consistent with HSPA5 suppression in TNF-injected MGs ( P < 0.01) and MECs treated with TNF in vitro ( P < 0.01). Moreover, obesity increased lysosomal activity ( P < 0.05) and autophagy in the MG, which corresponded to increased zinc transporter 2 abundance and lysosomal zinc concentration compared with lean mice (obese: 0.20 ± 0.02 μg Zn/mg protein; lean: 0.14 ± 0.01 μg Zn/mg protein; P < 0.05). Importantly, MGs of obese mice exhibited markers of apoptosis ( P = 0.05) and involution ( P < 0.01), which were not observed in lean mice. Conclusions: Diet-induced obesity created a proinflammatory MG microenvironment in mice, which was associated with zinc-mediated ER stress and autophagy and the activation of premature involution.